1985
DOI: 10.2135/cropsci1985.0011183x002500060007x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Root Characters and their Relations to Drought Resistance in Rice1

Abstract: The ability of rice plants to tolerate drought stresses is associated with root system characters. However, the genetics of root traits are not well understood. Hence, the inheritance of six root characters of rice (Oryza sativa L.) was studied using the parents, F1, F2, and F3 populations of the cross IR20✕MGL‐2. Plants were grown in a hydroponic culture solution in a phytotron glasshouse and in an upland drought screening nursery. A polygenic system of inheritance was indicated for the root characters. The F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
0
2

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(90 citation statements)
references
References 0 publications
6
82
0
2
Order By: Relevance
“…Increased carbon supply to roots (Aguirrezabal et al, 1993;Bingham and Stevenson, 1993) or exogenous applications of plant growth regulators (Torrey, 1986), have been shown to increase root branching. However, such morphological adaptations of deep roots have not previously been characterized among relevant genetic materials according to the level of water stress, in spite of many genetic studies on rice roots (Ekenayake et al, 1985 ;Loresto and Chang, 1994) . By new molecular techniques, we may now be able to identify quantitative trait loci ( QTL) for such adaptive root traits under differing water-stress levels, which could be helpful in incorporating such traits into elite cultivars for improvement of drought tolerance.…”
Section: Adaptive Root Traitsmentioning
confidence: 99%
“…Increased carbon supply to roots (Aguirrezabal et al, 1993;Bingham and Stevenson, 1993) or exogenous applications of plant growth regulators (Torrey, 1986), have been shown to increase root branching. However, such morphological adaptations of deep roots have not previously been characterized among relevant genetic materials according to the level of water stress, in spite of many genetic studies on rice roots (Ekenayake et al, 1985 ;Loresto and Chang, 1994) . By new molecular techniques, we may now be able to identify quantitative trait loci ( QTL) for such adaptive root traits under differing water-stress levels, which could be helpful in incorporating such traits into elite cultivars for improvement of drought tolerance.…”
Section: Adaptive Root Traitsmentioning
confidence: 99%
“…In general, the roots of upland rice cultivars are morphologically thicker and penetrate more deeply than those of lowland cultivars. These traits are controlled by multiple genes (Ekanayake et al 1985). Many analyses of quantitative trait loci (QTLs) of root morphological traits have been carried out using different mapping populations (reviewed by Price et al 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also have elucidated structural adaptations of root architecture to overcome drought stress. For example, rice inbred lines (IR20 3 MGL-2) with long, thick roots showed enhanced drought tolerance (Ekanayake et al, 1985), and root-specific overexpression of OsNAC10 promoted radial root growth, which in turn enhanced drought tolerance . In addition, overexpression of DEEPER ROOTING1 conferred drought avoidance capacity by altering rice root architecture (Uga et al, 2013), while drought stress was reported to cause an accumulation of lignin in roots, thereby modifying cell wall architecture to enhance growth under drought conditions (Yoshimura et al, 2008).…”
mentioning
confidence: 99%